Social identity in people with multiple sclerosis: a meta-synthesis of qualitative research. Issue 4 (4th November 2014) - B. Barker, Alex; das Nair, Roshan; B. Lincoln, Nadina; Hunt, Nigel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Many aspects of the self are lost as a consequence of having multiple sclerosis (MS). A person's identity can be altered by negative self-concepts, which are associated with poor psychological wellbeing and can lead individuals to reconstruct their sense of self. The Social Identity Model of Identity Change argues that previously established identities form a basis of continued social support, by providing grounding and connectedness to others to facilitate the establishment of new identities. Family support is a salient factor in adjustment to MS and may enable the establishment of new identities. The purpose of this paper is to investigate identity reconstruction following a diagnosis of MS. Design/methodology/approach – A meta-synthesis of the qualitative literature was conducted to examine the relationship between identity change and family identity of people with MS and other family members. Findings – In all, 16 studies were identified that examined identity change and the family following a diagnosis of MS. Coping strategies used by people with MS and their wider family groups, affect the reconstruction of people's identity and the adjustment to MS. Receiving support from the family whilst a new identity is constructed can buffer against the negative effects of identity loss. Practical implications – The family base is strengthened if MS-related problems in daily life are adapted into the individual and family identity using positive coping styles. Originality/value – This review provides an interpretation and explanation for results of previous qualitative studies in this area.